The Impact of Teachers’ Verbal and Non-Verbal Communication on Students’ Motivation in Learning English - Megawati, Wahyu; Hartono, Rudi (English Education Journal, 2020)
The objectives of this study are to explain the use of teachers’ verbal communication, teachers’ non-verbal communication, and the impact of teachers’ verbal communication and non-verbal communication on students' motivation in learning English.This study used the framework of teachers’ talk proposed by Sinclair and Brazil (1985) and Wang and Loewen (2015) to analyze the teachers’ verbal communication and non-verbal communication in the English classroom. Data were taken from lesson transcripts and teachers’ behaviors from the video recordings. Using the teachers’ utterances and teachers’ behaviors as the unit of analysis, procedures of analyzing data include: organizing and preparing the data, coding, describing, and interpreting. To validate the findings, initial results of the analysis had been examined by data source triangulation and using focused group discussion. Findings showed that the most-used teachers’ verbal communication is questioning while the most-used teachers’ non-verbal communication is hand movements and facial expressions. The most-motivating teachers’ verbal communication is questions and the most-motivating teachers’ non-verbal communication comes from facial expressions.